2012
DOI: 10.3393/jksc.2012.28.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Recurrent Rectourethral Fistula by Using Transanal Rectal Flap Advancement and Fibrin Glue: A Case Report

Abstract: Rectourethral fistulas (RUFs) in adults are rare and could result from complicated trauma, and prostatic or rectal surgery. RUFs have been treated initially by using primary repair and omental interposition with or without a colostomy during surgery. Recurrent RUFs require complex surgery, such as a low rectal resection and coloanal anastomosis, an interposition flap of the datos muscle or gracilis muscle, and others. Recently, transanal rectal flap advancement and fibrin glue injection have provided an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Only case studies of fibrin glue and fulguration of RUF have been reported, however, none post ablative therapy 14–16. These articles report good outcomes with no complications from the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Only case studies of fibrin glue and fulguration of RUF have been reported, however, none post ablative therapy 14–16. These articles report good outcomes with no complications from the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After diversion, spontaneous closure has been reported to be 14%–46.5%. 4 Fecaluria is known to be a poor prognostic sign, indicating that the fistula may be large in size and difficult to heal. Different methods of treatment are described in literature, like diversion, surgical procedures like perineal approach with dartos pedicled flap, posterior sagittal approach, transanal approach, posterior trans-sphincteric approach or modified York-Mason method, use of rectal advancement flaps, gracilis flaps or omental transposition.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies advocate fecal and urinary diversion as the initial treatment in the management of an RUF because diversion may provide better conditions to safely dissect the plane between the rectum and the urethra by controlling the local inflammation and contamination around the fistula [ 9 ]. However, the spontaneous closure rate for RUF after diversion only has been reported to be 14% to 46.5% [ 10 , 11 ], implying that a staged and definitive surgical treatment is necessary in the majority of the patients. This was obviously shown in our study because during a mean 12 months observational period, no spontaneous closures were observed in patients who underwent only a diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Complete closure of the fistula was attained as well. Recently, less invasive procedures using bioglue to supplement poor visualization and instrumentalization of the transanal approach have also been described in some case reports [ 10 ], but the effectiveness of those procedures should be determined with further studies.…”
Section: Discussionmentioning
confidence: 99%